Composition and functional properties of hemp seed protein isolates from various hemp cultivars. Issue 3 (24th January 2023) - Liu, Martin; Toth, Jacob A.; Childs, Mackenzie; Smart, Lawrence B.; Abbaspourrad, Alireza
Abstract: Hemp seed protein isolates (HPI) were extracted from seven commercial hemp cultivars, a Cornell breeding line, and a commercial hemp heart product, and their composition and functional properties were investigated. HPI contained different ratios of edestin, vicilin, and albumin proteins, which affected protein solubility and functionality. Higher protein solubility was associated with cultivars that contained more vicilin and albumin, which influenced the subsequent functional properties of HPI. Significant differences in water holding capacity (0.83–1.05 g water/g protein isolate), oil holding capacity (1.28–1.81 g oil/g protein isolate), foam capacity (52.9%–84.9%), and foam stability (68.1%–89.4%) were observed across HPI. The Cornell hemp breeding line exhibited the highest protein solubility at pH 7.0 and was uniquely capable of forming an emulsion. The relationship identified between hemp seed protein composition and functionality, in conjunction with the demonstration of an on‐going hemp breeding line, suggest that continued, targeted development of hemp cultivars can improve its seed protein functional properties for ingredient utilization in plant‐based foods.